THUR 084 Cranial autonomic symptoms in cluster headache induced by nitroglycerin. Issue 10 (13th September 2018) - Wei, DY; Goadsby, PJ
Abstract : Introduction: Cluster headache (CH) is characterised by attacks of unilateral excruciating headache, ipsilateral cranial autonomic symptoms (CAS) and/or agitation. Studying of CAS can further our understanding of CH pathophysiology, but is limited by the episodic nature of the disease. Nitroglycerin (NTG) is known to induce CH. The aim of this study is to characterise CAS induced by NTG. Methods: CH patients received intravenous NTG 0.5 mcg/kg/min over 20 min. CAS and headache phenotype were recorded. The study was approved by the NHS Research Ethics Committee. Results: Twenty-three patients participated: 83% male and 61% episodic cluster headache. The most common spontaneous CAS reported were lacrimation, nasal congestion and conjunctival injection. Agitation was reported in 96%. Nitroglycerin induced ipsilateral CAS in 91% of the patients, with 74% with ipsilateral pain. Most commonly induced CAS were nasal congestion, lacrimation and periorbital swelling. Agitation was reported in 61%. The majority of the CAS (80%) induced by NTG presented before the onset of severe pain. Conclusion: We demonstrate that NTG effectively triggers ipsilateral cranial autonomic symptoms in CH patients and that they often present in a phase before the onset of pain reflecting the underlying pathways during a cluster headache attack.